Techniques for high-performance distributed computing in computational fluid mechanics - Dalcin, Lisandro Daniel (2008)
Fil: Dalcin, Lisandro Daniel. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.